Indoor air quality and wildfire smoke impacts in the Pacific Northwest. (7th February 2018) - Kirk, W. Max; Fuchs, Madeline; Huangfu, Yibo; Lima, Nathan; O'Keeffe, Patrick; Lin, Beiyu; Jobson, Tom; Pressley, Shelley; Walden, Von; Cook, Diane; Lamb, Brian K.
Abstract : Efforts to improve energy efficiency in homes and buildings have led to tighter structures. However, these changes can also produce negative consequences for indoor air quality and human health. One of the dramatic effects of climate change and weather is the increase in destructive wildfires, such as those experienced in the Pacific Northwest during the summer of 2015. The current article presents data for measurements at two houses during periods with and without high levels of wildfire smoke outdoors. For each house, indoor and outdoor pollutant measurements were obtained for ozone (O3 ), fine particulate matter (PM2.5 ), and volatile organic compounds along with outdoor weather conditions and occupant activities including the use of windows and doors. The volatile organic compound measurements were obtained using a Proton Transfer Reaction Mass Spectrometer. Compounds monitored included acetonitrile (a biomass burning tracer), formaldehyde, acetaldehyde, methanol, acetone, benzene, toluene, and C2-alkylbenzenes (i.e., sum of xylenes and ethylbenzene), C3-alkylbenzenes (i.e., sum of trimethylbenzene, ethyltoluene, and propylbenzene isomers), and C4-alkylbenzenes (i.e., sum of tetramethylbenzene and its isomers). A carbon dioxide tracer method was used to measure in situ ventilation rates, and blower door tests were also completed to determine standard ventilation rates. For smoky periods with elevated outdoor pollutant levels, penetration factors, defined as the ratio of indoor/outdoor concentrations were quite low. Penetration factors for PM2.5 were 11% for H2 and 15% for H3, except when windows or doors were open. The penetration factors for O3 were also low at 24% for H2 and 5% for H3. Elevated indoor volatile organic compound levels were not typically associated with outdoor levels, but reflected significant indoor sources. During smoke events, acetonitrile, a biomass burning tracer compound, was elevated outdoors and indoors in both houses, and benzene was elevated outdoors and indoors in H3.